Strategy Ofdevelopment Institution Conservation In The Segati Villagesub-District Langgam, Districtpelalawan Province Riau - Rosady, Eni Rita; Yoza, Defri; ', M. Mardhiansyah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The collaboration of forest management between Segati community andcompany, accomplished inaVillage Conservation Institution.LKDSegatiisaninstitutionmanagesÂ  bythe community. LKD Segati has the visionandmission ofmanaging nature to increasepublic revenues,economic development alternativesandcreate new jobs, andundertakesustainablemanagement ofprotected areas.This study aimstoidentifythe potentialand theproblems faced byLKDSegati, andformulatealternativedevelopmentstrategyLKDSegati. SWOTanalysisis usedtoformulatethe company strategyfactorswithSWOTmatrix.Thismatrixillustrates clearlyhow theexternalopportunities andthreatsfaced byLKDSegatican be customizedwithitsstrengthsandweaknesses. Potential of theLKDSegatithathasofficers and members, strategic location, hasalegalinstitution, support ofcompaniesandNGO'scounterpart, andhaveaccess tothe conservation area.Problems faced byLKDSegatiisstilllowhuman resourcescapacity,weakmanagementinstitutions, lack offinancial resources, andinadequatefacilities.The results of this study showedthatdevelopmentstrategycan beappliedinLKDSegatiisa)improvinghuman resourcecapacitybytraininggradually throughcorporatesupport, NGO/government, b) to maintainandimprove theexistingprogramactivitiesthrough thesupport ofcompanies, c)increasecooperationwiththegovernments, company and community, d) improveagencymanagementsystem, e) using the potentialSDA/SDHandthe environmenttobe abusiness opportunity. Keywords: Strategy, conservation institutions, development, SWOT analysis.